(untitled) (Journal of Mathematical Study, 2017)
In this paper we use the maximum principle and the Hopf lemma to prove symmetry results to some overdetermined boundary value problems for domains in the hemisphere or star-shaped domains in S^n. Our method is based on finding suitable P-functions as Weinberger ([26]).